Analysis of Slang Words Used by Main Character in “Senior Year” Movie - Putri, Ni Kadek Ayu; Pratiwi, Desak Putu Eka (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to determine the type of slang and social factors that influence the slang spoken by the main character in the movie Senior Year. The data were analyzed using qualitative and quantitative methods using theories from Allan and Burridge (2006) to identify the types of slang found and Holmes (2013) used in analyzing the social factors that influence the slang used. The data were collected through observation method. The results showed that there are 8 or 36,4% for fresh and creative, 4 or 18,3% for clipping, 4 or 18,2% for imitative, 3 or 13,6% for flippant, and 3 or 13,6% for acronym. It is shown that the highest percentage of types of slang is fresh and creative, which is 36,4%. In analyzing the data, the researcher found that the social factors influenced the slang utterances. Participants influence the slang spoken to another people, function influence the goal of the slang, setting influence the place and situation of the slang used, and topic influence the main point of the conversation.